The Practicality of Plane and Space Geometry Textbook as Teaching Materials in Mathematics Education Department of UMRAH - Rezky Ramadhona; Nur Asma Riani Siregar; Okta Alpindo (Universitas Maritim Raja Ali Haji, 2023)
This study aims to produce teaching materials in the Geometry of Plane and Space course integrated with the maritime context of the Riau Islands. This research is a solution to problems arising from a need for teaching materials to the characteristics of students in the Mathematics Education Department of UMRAH. The 4D model (Define, Design, Development, and Disseminate) is used as the research development model. The research has reached the final activity of the Development stage, namely the practicality test of textbooks produced. The instrument used in the practicality test is a practicality questionnaire with a Likert scale. The evaluation results show that the textbooks produced through this development research have met the applicable criteria for use as teaching materials, with an achievement level of 72,85%. Thus, the textbook produced with the title Plane and Space Geometry Textbook has met the practical to use as teaching material in the Geometry of Plane and Space course. Integrating the maritime context of the Riau Islands helps students connect the content of teaching materials with their daily life. It helps them more easily understand the new knowledge.